Polarizing plate with phase difference layer and image display device

By using a specific phase differential layer and adhesive layer design in the polarizer of the phase differential layer, the problem of insufficient durability in the existing technology is solved, and higher durability and stability are achieved.

CN119355862APending Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202410996238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-24
Filing Date
2024-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, polarizers with phase difference layers are not durable when used in harsh environments, and it is difficult to meet more stringent environmental needs.

Method used

The polarizer containing the vertical part, with the first and second phase differential layers, has a specific refractive index characteristics, and through a specific adhesive layer design Higher than the first adhesive layer to inhibit the stress caused by changes in dimensions.

Benefits of technology

Through this design, the durability of the polarizer with the retardation layer is significantly improved, making it perform better in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355862A_ABST
    Figure CN119355862A_ABST
Patent Text Reader

Abstract

The invention provides a polarizing plate with a phase difference layer and an image display device. The polarizing plate has excellent anti-reflection characteristics. A polarizing plate with a phase difference layer according to an embodiment of the present invention has, in the following order: a polarizing plate including a polarizer; a first phase difference layer; a first adhesive layer; a second phase difference layer; and a second adhesive layer, the refractive index characteristic of the first phase difference layer shows the relationship of nz > nx = ny, the refractive index characteristic of the second phase difference layer shows the relationship of nx > ny > = nz, the first phase difference layer and the second phase difference layer are resin films, and the storage modulus G 'AD2 of the second adhesive layer exceeds 0.15 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate with a phase difference layer and an image display device. Background Art

[0002] Image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) are rapidly becoming popular. In these image display devices, polarizing plates with phase difference layers are used for the purpose of improving display characteristics and preventing reflection.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-66882 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In recent years, image display devices are used in various environments and are required to have durability in more severe environments. A main object of the present invention is to provide a polarizing plate with a retardation layer having excellent durability.

[0008] Means used to solve problems

[0009] 1. A polarizing plate with a phase difference layer according to an embodiment of the present invention comprises, in order: a polarizing plate including a polarizer; a first phase difference layer; a first adhesive layer; a second phase difference layer; and a second adhesive layer, wherein the refractive index characteristic of the first phase difference layer shows a relationship of nz>nx=ny, and the refractive index characteristic of the second phase difference layer shows a relationship of nx>ny≥nz, the first phase difference layer and the second phase difference layer are resin films, and the storage modulus G' of the second adhesive layer is AD2 More than 0.15MPa.

[0010] 2. The polarizing plate with a retardation layer described in 1 above may be formed by laminating the polarizer and the first retardation layer via an adhesive layer.

[0011] 3. In the polarizing plate with a phase difference layer described in 1 or 2 above, the Re (550) of the second phase difference layer is 120nm~170nm, and the angle between the slow axis of the second phase difference layer and the absorption axis of the polarizer can be 40°~50° or 130°~140°.

[0012] 4. In the polarizing plate with a retardation layer according to any one of 1 to 3 above, the second retardation layer may be a resin film containing a polycarbonate-based resin.

[0013] 5. In the polarizing plate with a retardation layer according to any one of 1 to 4 above, the storage modulus G′ of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 Can satisfy G' AD2 >G' AD1 relationship.

[0014] 6. The polarizing plate with a retardation layer according to any one of 1 to 5 above can be used in an organic electroluminescent display device.

[0015] 7. In another aspect of the present invention, an image display device is provided. The image display device includes the polarizing plate with a retardation layer according to any one of 1 to 6 above.

[0016] 8. The image display device described in 7 above may be an organic electroluminescent display device.

[0017] Effects of the Invention

[0018] According to the embodiment of the present invention, a polarizing plate with a retardation layer having better durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic cross-sectional view of a polarizing plate with a retardation layer in one embodiment of the present invention.

[0020] Explanation of symbols

[0021] 10 Polarizer

[0022] 11 Polarizer

[0023] 12. Protective layer

[0024] 21. First phase difference layer

[0025] 22. Second phase difference layer

[0026] 31 first adhesive layer

[0027] 32 Second adhesive layer

[0028] 100 Polarizing film with phase difference layer DETAILED DESCRIPTION

[0029] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. In order to make the description clearer, the accompanying drawings sometimes schematically show the width, thickness, shape, etc. of each part compared with the embodiment, but it is always just an example and does not limit the interpretation of the present invention. In this specification, (meth)acrylic group refers to acrylic group and / or methacrylic group. In addition, in this specification, "to" indicating a numerical range includes the numerical value of its upper limit and lower limit.

[0030] (Definition of terms and symbols)

[0031] The definitions of terms and symbols in this specification are as follows.

[0032] (1) Refractive index (nx, ny, nz)

[0033] “nx” is the refractive index in the direction where the refractive index in the plane reaches the maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.

[0034] (2) In-plane phase difference (Re)

[0035] "Re(λ)" is the in-plane phase difference measured by light of wavelength λnm at 23°C. For example, "Re(550)" is the in-plane phase difference measured by light of wavelength 550nm at 23°C. Re(λ) is obtained by the formula: Re(λ) = (nx-ny) × d when the thickness of the layer (film) is set to d (nm).

[0036] (3) Retardation in the thickness direction (Rth)

[0037] "Rth(λ)" is the phase difference in the thickness direction measured by light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured by light of wavelength 550nm at 23°C. Rth(λ) is obtained by the formula: Rth(λ) = (nx-nz) × d when the thickness of the layer (film) is set to d (nm).

[0038] (4) Nz coefficient

[0039] The Nz coefficient is obtained by Nz=Rth / Re.

[0040] (5) Angle

[0041] In this specification, when an angle is mentioned, the angle includes both clockwise and counterclockwise rotation relative to a reference direction. Therefore, for example, "45°" means 45° clockwise rotation and 45° counterclockwise rotation.

[0042] A. Polarizing plate with phase difference layer

[0043] The polarizing plate with phase difference layer of the embodiment of the present invention has: a polarizing plate including a polarizer; a first phase difference layer; a first adhesive layer; a second phase difference layer; and a second adhesive layer. The refractive index characteristic of the first phase difference layer shows a relationship of nz>nx=ny, and the refractive index characteristic of the second phase difference layer shows a relationship of nx>ny≥nz. The first phase difference layer and the second phase difference layer are resin films. The storage modulus G' of the second adhesive layer AD2 By setting it as such a structure, the polarizing plate with a retardation layer which is excellent in durability can be provided.

[0044] A-1. Overall structure of polarizing plate with retardation layer

[0045] Figure 1 It is a schematic cross-sectional view of a polarizing plate with a phase difference layer according to an embodiment of the present invention. The polarizing plate 100 with a phase difference layer has, in order: a polarizing plate 10 including a polarizer 11; a first phase difference layer 21; a first adhesive layer 31; a second phase difference layer 22; and a second adhesive layer 32. The polarizing plate 10 further includes: a polarizer 11, and a protective layer 12 arranged on the side of the polarizer 11 opposite to the side on which the first phase difference layer 21 is arranged. The polarizer 11 may be further laminated with a protective layer (not shown) on the side on which the protective layer 12 is not laminated. In the example shown in the figure, no protective layer is arranged between the polarizer 11 and the first phase difference layer 21, and the first phase difference layer 21 is arranged adjacent to the polarizer 11 via any appropriate adhesive layer or adhesive layer. According to an embodiment of the present invention, even in the case where the protective layer arranged on the first phase difference layer side is omitted, the first phase difference layer 21 as a resin film can function as a protective layer for the polarizer 11. Therefore, the durability of the polarizing plate 100 with a phase difference layer can be ensured. In addition, it can contribute to the thinning of the polarizing plate 100 with a phase difference layer. The refractive index characteristics of the first phase difference layer 21 show a relationship of nz>nx=ny, and the refractive index characteristics of the second phase difference layer 22 show a relationship of nx>ny≥nz. The first phase difference layer 21 and the second phase difference layer 22 are resin films. The first phase difference layer 21 and the second phase difference layer 22 are stacked via the first adhesive layer 31. In addition, the second adhesive layer 32 is stacked on the side of the second phase difference layer 22 that is not in contact with the first adhesive layer 31. Typically, the component of the image display panel such as a reflector is bonded via the second adhesive layer 32. The storage modulus G' of the second adhesive layer 32 AD2More than 0.15MPa. When the polarizer 100 with a phase difference layer is placed in a heated environment, the polarizer 11 and the second phase difference layer 22 will undergo dimensional changes. When configured in an image display device, the second phase difference layer 22 can be fixed to a reflector. As a result, stress caused by dimensional changes will easily accumulate in the second phase difference layer. When the phase difference layer undergoes dimensional changes, the optical properties change and the image display performance will decrease. Therefore, a polarizer with a phase difference layer having better durability is sought. As described above, in the polarizer with a phase difference layer of an embodiment of the present invention, the storage modulus G' of the adhesive layer (more specifically, the adhesive forming the adhesive layer) serving as the second adhesive layer AD2 More than 0.15MPa. If such an adhesive layer and a resin film are used as the first phase difference layer, the dimensional changes of the polarizer and the second phase difference layer can be suppressed. As a result, a polarizing plate with a phase difference layer having excellent durability can be provided. In this specification, the storage modulus G' refers to the value measured by a dynamic viscoelasticity measuring device at 25°C.

[0046] The storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 Preferably satisfy G' AD2 >G' AD1 If the storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 With the above relationship, it is possible to suppress the stress caused by the dimensional change of the polarizer from being transferred to the second phase difference layer. In addition, the dimensional change of the second phase difference layer itself can also be suppressed. As a result, a polarizing plate with a phase difference layer having better durability can be provided.

[0047] Storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 The difference (G' AD2 -G' AD1 ) is preferably 0.0 MPa to 2.0 MPa, more preferably 0.02 MPa to 1.5 MPa, and further preferably 0.06 MPa to 1.0 MPa. If the storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 The difference (G' AD2 -G' AD1 ) is within the above range, the stress caused by the dimensional change of the polarizer applied to the second phase difference layer can be suppressed. In addition, the dimensional change of the second phase difference layer itself can also be suppressed. As a result, a polarizing plate with a phase difference layer having better durability can be provided.

[0048] As described above, the polarizing plate 100 with a phase difference layer can be attached to an image display panel included in an image display device via the second adhesive layer 32, for example. In practical terms, a release liner can be attached to the surface of the second adhesive layer 32. The release liner can be temporarily attached until the polarizing plate with a phase difference layer is used. By using a release liner, a roll of the polarizing plate 100 with a phase difference layer can be formed while protecting, for example, the second adhesive layer 32.

[0049] The polarizer 100 with a phase difference layer may further have other functional layers not shown. The types, characteristics, quantity, combination, configuration, etc. of other functional layers that the polarizer with a phase difference layer can have can be appropriately set according to the purpose. For example, the polarizer with a phase difference layer may further have a conductive layer or an isotropic substrate with a conductive layer. The polarizer with a phase difference layer having an isotropic substrate with a conductive layer or a conductive layer is suitable for a so-called internal touch panel input display device in which a touch sensor is assembled inside an image display panel. In addition, as another example, the polarizer with a phase difference layer may further have other phase difference layers. The optical properties (e.g., refractive index characteristics, in-plane phase difference, Nz coefficient, photoelastic coefficient), thickness, configuration, etc. of other phase difference layers can be appropriately set according to the purpose. As a specific example, other phase difference layers (representatively, layers that impart (elliptical) circular polarization function and layers that impart ultra-high phase difference) that improve visual recognition when visually recognized through polarized sunglasses can be provided on the visual recognition side of the polarizer. By providing such a layer, even when the display screen is viewed through polarizing lenses such as polarizing sunglasses, excellent visibility can be achieved, and it can be preferably applied to an image display device that can be used outdoors.

[0050] The various components constituting the polarizer 100 with a phase difference layer are typically stacked via any appropriate adhesive layer. As specific examples of the adhesive layer, an adhesive layer and an adhesive layer can be cited. Although not shown in the figure, the protective layer 12 is attached to the polarizer 11, for example, via an adhesive layer (preferably using an active energy ray-curing adhesive). In addition, for example, the polarizer 10 and the first phase difference layer 21 can be stacked via an adhesive layer (preferably using an active energy ray-curing adhesive) or via an adhesive layer (preferably using an acrylic adhesive). The thickness of the adhesive layer is, for example, greater than 0.1 μm, preferably 0.3 μm to 5 μm, and more preferably 0.5 μm to 3 μm. The thickness of the adhesive layer is, for example, greater than 3 μm, preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm.

[0051] The total thickness of the polarizer with a phase difference layer is, for example, less than 150 μm, preferably less than 100 μm, and for example, more than 30 μm, preferably more than 60 μm. In addition, the total thickness of the polarizer with a phase difference layer refers to the total thickness of the polarizer, the first phase difference layer and the second phase difference layer, the first adhesive layer and the second adhesive layer, and the adhesive layer for stacking them (that is, the total thickness of the polarizer with a phase difference layer does not include the thickness of the release liner that can be temporarily attached to the surface of the second adhesive layer).

[0052] The polarizer 100 with a phase difference layer can be in the form of a single sheet or a strip. In this specification, "strip" refers to an elongated shape that is very long relative to the width, for example, including an elongated shape that is 10 times or more, preferably 20 times or more long relative to the width. The elongated laminate can be wound into a roll.

[0053] B. Polarizer

[0054] The polarizing plate 10 includes a polarizer 11. The polarizing plate preferably further includes a protective layer 12 on the side of the polarizer 11 opposite to the side where the first retardation layer 21 is arranged. The polarizing plate 10 may include a protective layer on the side of the polarizer 11 where the first retardation layer 21 is arranged, if necessary.

[0055] B-1. Polarizer

[0056] The polarizer 11 is typically a resin film containing a dichroic substance (eg, iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formaldehyde-treated PVA films, and partially saponified ethylene-vinyl acetate copolymer films.

[0057] The thickness of the polarizer is, for example, 18 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and further preferably 8 μm or less. The thickness of the polarizer is preferably 1 μm or more.

[0058] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 40.0% to 46.0%, preferably 41.0% to 45.0%, and more preferably 41.5% to 44.5%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.

[0059] The polarizer can be produced by any appropriate method. Specifically, the polarizer can be produced from a single-layer resin film or a laminated body including a substrate.

[0060] The method for making a polarizer from the above-mentioned monolayer resin film typically includes dyeing and stretching the resin film with dichroic substances such as iodine and dichroic dyes. As the resin film, for example, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers are used. The method can further include insolubilization treatment, swelling treatment, crosslinking treatment, etc. Such a manufacturing method is a well-known customary method in the art, so detailed description is omitted.

[0061] The polarizer obtained using the laminate containing the above-mentioned substrate can be made, for example, using a laminate of a resin substrate and a resin film or a resin layer (representatively a PVA-based resin layer). Specifically, it can be made by the following steps: a PVA-based resin solution is applied to a resin substrate, and the PVA-based resin layer is formed on the resin substrate after drying, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer a polarizer. In the present embodiment, it is preferred that a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. In addition, the stretching may further include stretching the laminate in the air at a high temperature (for example, above 95°C) before the stretching in the aqueous boric acid solution as required. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment by being heated while being conveyed in the length direction, thereby shrinking it by more than 2% in the width direction. Representatively, the manufacturing method of this embodiment includes: applying an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment and a drying shrinkage treatment to the laminate in sequence. By introducing the auxiliary stretching, even when PVA is coated on the thermoplastic resin, the crystallinity of PVA can be improved, and high optical properties can be achieved. In addition, by improving the orientation of PVA in advance, when immersed in water in the subsequent dyeing process and stretching process, the problems of reduction and dissolution of the orientation of PVA can be prevented, and high optical properties can be achieved. In addition, when the PVA-based resin layer is immersed in the liquid, compared with the case where the PVA-based resin layer does not contain a halide, the orientation disorder of the PVA molecules and the reduction of the orientation can be suppressed, and high optical properties can be achieved. In addition, the laminate is shrunk in the width direction by the drying shrinkage treatment, thereby achieving high optical properties. A protective layer is laminated on the peeling surface after peeling off the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeling surface, so that a polarizer can be obtained. The details of the method for producing such a polarizer are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.

[0062] B-2. Protective layer

[0063] The protective layer 12 can be formed of any appropriate resin film that can be used as a protective layer of a polarizer. Specific examples of the resin as the main component of the resin film include cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (meth) acrylic resins, acetate resins, etc.

[0064] The polarizing plate 100 with a retardation layer is typically disposed on the visual recognition side of the image display device, and the protective layer 12 is disposed on the visual recognition side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coating (HC), anti-reflection treatment, anti-blocking treatment, anti-glare treatment, etc. as required.

[0065] The thickness of the protective layer is, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. When the surface treatment is performed, the thickness of the protective layer includes the thickness of the surface treatment layer.

[0066] C. Phase difference layer

[0067] C-1. First phase difference layer

[0068] The first phase difference layer 21 is a so-called positive C plate whose refractive index characteristic shows the relationship of nz>nx=ny. If a positive C plate is arranged between the polarizer and the second phase difference layer whose refractive index characteristic shows the relationship of nx>ny≥nz, it is possible to prevent reflection in the oblique direction very well, and further widen the viewing angle of the anti-reflection function. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the first phase difference layer can be less than 10nm.

[0069] The retardation Rth(550) in the thickness direction of the first retardation layer is preferably -70 nm to -165 nm, more preferably -80 nm to -155 nm, further preferably -90 nm to -145 nm, particularly preferably -100 nm to -135 nm.

[0070] The first phase difference layer preferably has a puncture modulus of 50 g / mm or more, more preferably 52 g / mm or more, and further preferably 55 g / mm or more. The puncture modulus of the first phase difference layer is, for example, 200 g / mm or less. If the puncture modulus of the first phase difference layer is within the above range, the dimensional change of the second phase difference layer (for example, the expansion and contraction of the second phase difference layer formed by the stretched film of the resin film, etc.) can be preferably suppressed. In this specification, the puncture modulus refers to: the force (g) before the phase difference film is about to break (or crack) when the needle (puncture tool) pierces the main surface of the phase difference film (for example, the first phase difference layer) vertically, divided by the strain (mm) at this time. As a needle, a needle with a top diameter of 1 mmφ and 0.5R can be used. The speed of piercing the needle can be set to 0.33 cm / second. The puncture modulus can be measured by sandwiching the phase difference film between two plates with a circular hole of a diameter of less than 15 mm (for example, a diameter of 11 mm) through which the needle can pass. The puncture modulus can be measured at a temperature of 23°C. For example, the puncture modulus of 5 phase difference films is measured, and the average value thereof can be used as the puncture modulus of the phase difference film. The puncture modulus can be measured using a commercially available device. Examples of commercially available devices include a portable compression tester "KES-G5 Needle Penetration Force Measurement Standard" manufactured by Katotech Co., Ltd. and a small desktop tester "EZ Test" manufactured by Shimadzu Corporation.

[0071] As described above, the first phase difference layer is formed by a resin film. The phase difference layer can be roughly divided into an orientation solidification layer of a liquid crystal compound (liquid crystal orientation solidification layer) and a resin film according to its forming material. When the first phase difference layer adjacent to the polarizer is a liquid crystal orientation solidification layer, the polarizer sometimes deteriorates due to the influence of the liquid crystal compound, polymerization initiator, etc. contained in the liquid crystal orientation solidification layer. In contrast, when the first phase difference layer is a resin film, the deterioration of the polarizer can be appropriately prevented.

[0072] As the material of the resin film constituting the first phase difference layer, representative examples include resin materials with negative birefringence. A resin with negative birefringence is a resin that shows the property of reaching a maximum refractive index in a direction perpendicular to the stretching direction during uniaxial stretching. As a resin with negative birefringence, for example, a resin having chemical bonds and functional groups with large polarization anisotropy such as aromatic rings and carbonyl groups introduced into the side chains can be cited. As specific examples of resins with negative birefringence, acrylic resins, styrene resins, maleimide resins, modified polyolefin resins, fumarate resins, etc. can be cited. The above-mentioned resin materials can be used alone or in combination of two or more.

[0073] The acrylic resin can be obtained, for example, by addition polymerization of an acrylic ester monomer. Examples of the acrylic resin include polymethyl methacrylate (PMMA), polybutyl methacrylate, and polycyclohexyl methacrylate.

[0074] The styrene resin can be obtained, for example, by addition polymerization of styrene monomers. Examples of the styrene monomers include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, p-chlorostyrene, p-nitrostyrene, p-aminostyrene, p-carboxystyrene, p-phenylstyrene, 2,5-dichlorostyrene, and p-tert-butylstyrene.

[0075] The maleimide resin can be obtained, for example, by addition polymerization of a maleimide monomer. Examples of the maleimide monomer include N-ethylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-propylphenyl)maleimide, N-(2-isopropylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, and N-(2,6-dipropylphenyl)maleimide. Maleimide, N-(2,6-diisopropylphenyl)maleimide, N-(2-methyl-6-ethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-(2,6-dichlorophenyl)maleimide, N-(2-bromophenyl)maleimide, N-(2,6-dibromophenyl)maleimide, N-(2-biphenyl)maleimide, N-(2-cyanophenyl)maleimide, etc. Maleimide monomers can be obtained from Tokyo Chemical Industry Co., Ltd., etc.

[0076] In the above-mentioned addition polymerization, the birefringence characteristics of the obtained resin can also be controlled by substituting the side chain, or subjecting it to maleimide or grafting reaction after polymerization.

[0077] The above-mentioned resin having negative birefringence may also be copolymerized with other monomers. By copolymerizing other monomers, brittleness, formability, and heat resistance may be improved. Examples of such other monomers include olefins such as ethylene, propylene, 1-butene, 1,3-butadiene, 2-methyl-1-butene, 2-methyl-1-pentene, and 1-hexene; acrylonitrile; (meth)acrylates such as methyl acrylate and methyl methacrylate; maleic anhydride; vinyl esters such as vinyl acetate, and the like.

[0078] When the resin having negative birefringence is a copolymer of the styrene monomer and the other monomers, the blending ratio of the styrene monomer is preferably 50 mol% to 80 mol%. When the resin having negative birefringence is a copolymer of the maleimide monomer and the other monomers, the blending ratio of the maleimide monomer is preferably 2 mol% to 50 mol%. By blending within such a range, a resin film having excellent toughness and molding processability can be obtained.

[0079] As the above-mentioned resin with negative birefringence, preferably use styrene-maleic anhydride copolymer, styrene-acrylonitrile copolymer, styrene-(methyl) acrylate copolymer, styrene-maleimide copolymer, vinyl ester-maleimide copolymer, olefin-maleimide copolymer etc..The above-mentioned these can be used alone or in combination of two or more.These resins can show high negative birefringence, and excellent heat resistance.These resins can be obtained from Nova Chemical Japan Co., Ltd., Arakawa Chemical Industries, Ltd. etc. for example.

[0080] As the above-mentioned resin having negative birefringence, it is also preferred to use a polymer having a repeating unit shown by the following general formula (I). Such a polymer can show higher negative birefringence, and has excellent heat resistance and mechanical strength. Such a polymer can be obtained, for example, by using an N-phenyl substituted maleimide having a phenyl group having a substituent at least in the ortho position as the N substituent of the maleimide monomer of the starting material.

[0081]

[0082] In the above general formula (I), R1 to R5 independently represent hydrogen, a halogen atom, a carboxylic acid, a carboxylic ester, a hydroxyl group, a nitro group, or a straight-chain or branched alkyl or alkoxy group having 1 to 8 carbon atoms (wherein R1 and R5 are not hydrogen atoms at the same time), R6 and R7 represent hydrogen or a straight-chain or branched alkyl or alkoxy group having 1 to 8 carbon atoms, and n represents an integer greater than 2.

[0083] The resin having negative birefringence is not limited to those described above, and for example, resins having negative birefringence described in JP-A-2008-544304 and JP-A-2008-544317 can be used.

[0084] The resin film forming the first phase difference layer may also contain any appropriate additive as needed. Specific examples of additives include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, ultraviolet absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, thickeners, etc. The type and content of the additives can be appropriately set according to the purpose. The content of the additive in the resin film is, for example, about 3% to 10% by weight.

[0085] As a method for manufacturing the first retardation layer formed from the above resin film, any suitable manufacturing method can be used. In one embodiment, the resin film containing the above resin material can be directly used as the first retardation layer after film formation (i.e., in a non-stretched state). For example, if a resin solution containing the above resin material is used to form a film by a solution casting method, there is a tendency as follows: stress is generated on the support due to volume shrinkage during drying of the resin solution, and the molecular chains of the polymer are oriented in the in-plane direction. Thus, if a resin material with high birefringence performance and negative intrinsic birefringence is used, a coating film with large thickness-direction birefringence can be formed on the support due to the shrinkage effect during drying, and this coating film can be directly used as a positive C-plate.

[0086] The thickness of the first retardation layer is, for example, 1 μm to 40 μm, preferably 3 μm to 35 μm, and more preferably 5 μm to 30 μm.

[0087] C-2. Second retardation layer

[0088] The refractive index characteristics of the second retardation layer 22 show a relationship of nx > ny ≥ nz. In one embodiment, the second retardation layer can function as a λ / 4 plate. The in-plane retardation Re(550) of the second retardation layer is, for example, 120 nm to 170 nm, preferably 130 nm to 160 nm, and more preferably 140 nm to 150 nm. In addition, here "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range not impairing the effects of the present invention, it may sometimes be ny < nz. In addition, in this specification, a retardation layer with refractive index characteristics showing a relationship of nx > ny = nz is sometimes referred to as a positive A-plate, and a retardation layer with refractive index characteristics showing a relationship of nx > ny > nz is sometimes referred to as a negative B-plate.

[0089] The Nz coefficient of the second retardation layer is preferably 0.9 to 3, more preferably 0.9 to 2.5, further preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained polarizing plate with a retardation layer is used in an image display device, a very excellent reflected hue can be achieved.

[0090] The second retardation layer is arranged such that its slow axis forms an angle of, for example, 40° to 50° or 130° to 140°, preferably 42° to 48° or 132° to 138°, and more preferably approximately 45° or approximately 135° with the absorption axis of the polarizer 12. By forming such a configuration, a polarizing plate with a retardation layer having very excellent circular polarization characteristics (as a result, having very excellent antireflection characteristics) can be obtained.

[0091] The second phase difference layer can show an inverse wavelength dispersion characteristic in which the phase difference value increases as the wavelength of the measuring light increases, can show a positive wavelength dispersion characteristic in which the phase difference value decreases as the wavelength of the measuring light increases, or can show a flat wavelength dispersion characteristic in which the phase difference value hardly changes with the wavelength of the measuring light. In one embodiment, the second phase difference layer shows an inverse wavelength dispersion characteristic. At this time, Re(450) / Re(550) of the phase difference layer is, for example, greater than 0.8 and less than 1, preferably 0.8 to 0.95. If it is such a structure, a very excellent anti-reflection property can be achieved.

[0092] The second phase difference layer is a resin film, and preferably a stretched film of the resin film.

[0093] In one embodiment, the absolute value of the photoelastic coefficient of the second retardation layer is preferably 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, more preferably 1.0×10 -12 m 2 / N~1.2×10 - 11 m 2 / N resin. If the absolute value of the photoelastic coefficient is within such a range, the phase difference is unlikely to change when shrinkage stress is generated during heating. As a result, thermal unevenness of the obtained image display device can be well prevented.

[0094] As the resin contained in the above-mentioned resin film, polycarbonate resin, polyester carbonate resin, polyester resin, polyvinyl acetal resin, polyarylate resin, cyclic olefin resin, cellulose resin, polyvinyl alcohol resin, polyamide resin, polyimide resin, polyether resin, polystyrene resin, acrylic resin, etc. can be cited. These resins can be used alone or in combination (for example, blending, copolymerization). In the case where the second phase difference layer shows reverse wavelength dispersion characteristics, a resin film containing a polycarbonate resin or a polyester carbonate resin (hereinafter, sometimes referred to as a polycarbonate resin) can be preferably used.

[0095] As the above-mentioned polycarbonate resin, any appropriate polycarbonate resin can be used as long as the effect of the present invention can be obtained. For example, the polycarbonate resin contains: a structural unit from a fluorene dihydroxy compound; a structural unit from an isosorbide dihydroxy compound; and a structural unit from at least one dihydroxy compound selected from alicyclic diols, alicyclic dimethanols, di, tri or polyethylene glycols, and alkylene glycols or spiro glycols. Preferably, the polycarbonate resin contains: a structural unit from a fluorene dihydroxy compound, a structural unit from an isosorbide dihydroxy compound, a structural unit from alicyclic dimethanol and / or a structural unit from di, tri or polyethylene glycol; more preferably, it contains: a structural unit from a fluorene dihydroxy compound, a structural unit from an isosorbide dihydroxy compound, and a structural unit from di, tri or polyethylene glycol. The polycarbonate resin may also contain structural units from other dihydroxy compounds as needed. In addition, details of the polycarbonate-based resin that can be preferably used for the second phase difference layer and the method for forming the second phase difference layer are described in, for example, Japanese Patent Publication No. 2014-10291, Japanese Patent Publication No. 2014-26266, Japanese Patent Publication No. 2015-212816, Japanese Patent Publication No. 2015-212817, and Japanese Patent Publication No. 2015-212818, and the descriptions of these publications are cited in this specification as reference.

[0096] The thickness of the second retardation layer is preferably 100 μm or less. Specifically, the thickness of the second retardation layer composed of a stretched film of a resin film is, for example, 10 to 100 μm, preferably 10 to 70 μm, more preferably 10 to 60 μm, and further preferably 20 to 50 μm.

[0097] D. Adhesive layer

[0098] As mentioned above, the storage modulus G' of the second adhesive layer AD2 More than 0.15 MPa. In addition, the storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 Preferably satisfy G' AD2 >G' AD1 If the storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 With the above relationship, it is possible to suppress the stress caused by the dimensional change of the polarizer applied to the second phase difference layer. In addition, it is also possible to suppress the dimensional change of the second phase difference layer itself. As a result, a polarizing plate with a phase difference layer having better durability can be provided.

[0099] D-1. First adhesive layer

[0100] The first adhesive layer 31 is arranged between the first phase difference layer 21 and the second phase difference layer 22. The first adhesive layer can be formed by any appropriate adhesive. For example, as specific examples of adhesives constituting the adhesive layer, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives and polyether adhesives can be cited. By adjusting the type, quantity, combination and proportion of the monomers of the base resin forming the adhesive, as well as the amount of the cross-linking agent, the reaction temperature, the reaction time, etc., an adhesive having the desired properties corresponding to the purpose can be prepared. The base resin of the adhesive can be used only one, or two or more can be used in combination. The first adhesive layer and the second adhesive layer can be formed by the same adhesive, or by different adhesives. From the viewpoints of transparency, processability and durability, acrylic adhesives (acrylic adhesive compositions) are preferred.

[0101] The acrylic adhesive typically contains a (meth)acrylic polymer as a main component. The adhesive may contain the (meth)acrylic polymer in a proportion of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the adhesive.

[0102] The (meth)acrylic polymer contains an alkyl (meth)acrylate as a monomer unit as a main component. In addition, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in a ratio of preferably 80% by weight or more, more preferably 90% by weight or more in the monomer component forming the (meth)acrylic polymer. As the alkyl group of the alkyl (meth)acrylate, for example, a linear or branched alkyl group having 1 to 18 carbon atoms can be mentioned. The average number of carbon atoms of the alkyl group is preferably 3 to 9, more preferably 3 to 6.

[0103] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. As the silane coupling agent, for example, an epoxy-containing silane coupling agent may be mentioned. As the crosslinking agent, for example, an isocyanate crosslinking agent and a peroxide crosslinking agent may be mentioned. In addition, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. The details of the adhesive layer or the acrylic adhesive composition are, for example, recorded in Japanese Unexamined Patent Publication No. 2006-183022, Japanese Unexamined Patent Publication No. 2015-199942, Japanese Unexamined Patent Publication No. 2018-053114, Japanese Unexamined Patent Publication No. 2016-190996, and International Publication No. 2018 / 008712, and the records of these publications are cited in this specification as a reference.

[0104] Storage modulus G' of the first adhesive layer AD1(ie, the storage modulus of the adhesive forming the first adhesive layer) can be adjusted to any appropriate value. The storage modulus G' of the first adhesive layer AD1 If the storage elastic modulus of the first adhesive layer is within the above range, the stress caused by the dimensional change of the polarizer can be suppressed from being transferred to the second phase difference layer, thereby providing a polarizing plate with a phase difference layer having better durability.

[0105] The thickness of the first adhesive layer can be set to any appropriate value. The thickness of the first adhesive layer is preferably 2 μm to 25 μm, more preferably 3 μm to 20 μm, and further preferably 5 μm to 15 μm. If the thickness of the first adhesive layer is within the above range, the adhesion between the first phase difference layer and the second phase difference layer can be ensured. In addition, the stress caused by the dimensional change of the polarizer can be further suppressed from being transferred to the second phase difference layer.

[0106] D-2. Second adhesive layer

[0107] Storage modulus G' of the second adhesive layer AD2 (ie, the storage modulus of the adhesive forming the second adhesive layer) can be adjusted to any appropriate value. The storage modulus G' of the second adhesive layer AD2 If the storage modulus G' of the second adhesive layer is greater than 0.15 MPa, preferably 0.16 MPa to 2.0 MPa, and more preferably 0.17 MPa to 1.0 MPa. AD2 When the content is within the above range, the dimensional change of the second retardation layer can be suppressed, and a polarizing plate with a retardation layer having better durability can be provided.

[0108] The thickness of the second adhesive layer can be set to any appropriate value. The thickness of the second adhesive layer is preferably 10 μm to 40 μm, more preferably 12 μm to 35 μm, and further preferably 15 μm to 25 μm. If the thickness of the second adhesive layer is within the above range, the adhesion between the polarizer with a phase difference layer and the image display panel can be ensured. In addition, the dimensional change of the second phase difference layer can be suppressed, providing a polarizer with a phase difference layer with better durability.

[0109] Storage modulus G' of the second adhesive layer AD2 As long as it exceeds 0.15MPa, it can be formed by any appropriate adhesive. For example, the adhesive shown in the above examples can be used. In one embodiment, the second adhesive layer is formed using an adhesive composition comprising a (meth)acrylic polymer containing acrylic acid, (meth)acrylic acid alkyl ester and aromatic ring-containing monomer as monomer units and a polyether compound having a reactive silyl group.

[0110] Aromatic ring-containing monomers refer to compounds containing aromatic groups in their structures and containing polymerizable unsaturated double bonds such as (meth)acryloyl groups and vinyl groups. As aromatic groups, benzene rings, naphthalene rings, biphenyl rings, heterocycles, etc. can be mentioned. As heterocycles, morpholine rings, piperidine rings, pyrrolidine rings, piperazine rings, etc. can be mentioned. As such compounds, for example, (meth)acrylates containing aromatic groups can be mentioned. Aromatic ring-containing monomers can be used alone or in combination of two or more.

[0111] Specific examples of the (meth)acrylate containing an aromatic group include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy-3-phenoxy (Meth)acrylates having a benzene ring such as propyl (meth)acrylate, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, and polystyrene (meth)acrylate; (meth)acrylates having a naphthalene ring such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates having a biphenyl ring such as biphenyl (meth)acrylate. Examples of (meth)acrylates containing a heterocyclic ring include thiol (meth)acrylate, pyridinium (meth)acrylate, and pyrrole (meth)acrylate. In addition, examples of (meth)acrylic monomers containing a heterocyclic ring include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0112] Specific examples of the vinyl compound containing an aromatic group include vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl oxazole, vinyl morpholine, N-vinyl carboxamides, styrene, α-methylstyrene, and the like.

[0113] The aromatic ring-containing monomer may contain a functional group such as sulfonic acid in addition to a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the aromatic ring-containing monomer having such a functional group include styrenesulfonic acid and (meth)acryloyloxynaphthalenesulfonic acid.

[0114] As the aromatic ring-containing monomer, from the viewpoint of adhesive properties and durability, an aromatic group-containing (meth)acrylate is preferred, among which benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred, and benzyl (meth)acrylate is more preferred.

[0115] The content of the aromatic ring-containing monomer in the (meth)acrylic polymer is preferably 1 to 50% by weight, more preferably 1 to 35% by weight, further preferably 1 to 20% by weight, further preferably 7 to 18% by weight, and particularly preferably 10 to 16% by weight, based on 100% by weight of all the constituent monomers of the (meth)acrylic polymer.

[0116] As the monomer component other than the aromatic ring-containing monomer in the (meth)acrylic polymer, any appropriate monomer can be used, and examples thereof include the above-mentioned alkyl (meth)acrylates.

[0117] As the polyether compound, any appropriate compound having a polyether skeleton can be used. The polyether compound preferably has a polyether skeleton and has a general formula: -SiR a M 3-a Represented by a reactive silyl group (wherein, R is a monovalent organic group having 1 to 20 carbon atoms which may have a substituent, M is a hydroxyl group or a hydrolyzable group, and a is an integer of 1 to 3. When there are multiple Rs, the multiple Rs may be the same as or different from each other, and when there are multiple Ms, the multiple Ms may be the same as or different from each other).

[0118] The polyether skeleton possessed by the polyether compound preferably has a repeating structural unit of a linear or branched oxyalkylene group having 1 to 10 carbon atoms. The structural unit of the oxyalkylene group preferably has 2 to 6 carbon atoms, and more preferably has 3 carbon atoms. In addition, the repeating structural unit of the oxyalkylene group may be a repeating structural unit of one type of oxyalkylene group, or a repeating structural unit of a block unit or a random unit of two or more types of oxyalkylene groups. Examples of the oxyalkylene group include oxyethylene, oxypropylene, oxybutylene, and the like. Among these oxyalkylene groups, a structural unit having an oxypropylene group (particularly -CH2CH(CH3)O-) is preferred.

[0119] The polyether compound preferably has a main chain substantially formed by a polyether skeleton in addition to the above-mentioned reactive silyl group. Here, the main chain substantially formed by a polyoxyalkylene chain means that a small amount of other chemical structures may also be included. It means that as other chemical structures, for example, the chemical structure of the initiator in the case of manufacturing the repeating structural unit of the oxyalkylene involved in the polyether skeleton and the linking group with the reactive silyl group may also be included. The repeating structural unit of the oxyalkylene involved in the polyether skeleton is preferably 50% by weight or more, more preferably 80% by weight or more of the total weight of the polyether compound.

[0120] As the polyether compound, a commercially available product can be used. Specific examples of the polyether compound include: MS polymer S203, S303, S810 manufactured by KANEKA Corporation; SILYL EST250, EST280; SILYL SAT10, SAT200, SAT220, SAT350, SAT400; and EXCESTARS 2410, S2420, or S3430 manufactured by Asahi Glass Co., Ltd.

[0121] The content of the polyether compound in the adhesive composition is preferably 0.001 to 20 parts by weight relative to 100 parts by weight of the (meth)acrylic polymer. The content of the polyether compound is more preferably 0.01 parts by weight or more, further preferably 0.02 parts by weight or more, particularly preferably 0.1 parts by weight or more, and most preferably 0.5 parts by weight or more. In addition, the content of the polyether compound is more preferably 10 parts by weight or less, further preferably 5 parts by weight or less, and particularly preferably 3 parts by weight or less.

[0122] A pressure-sensitive adhesive containing a (meth)acrylic polymer and a polyether compound is described in, for example, Japanese Patent No. 4959014. The description of this publication is incorporated herein by reference.

[0123] E. Release liner

[0124] As the release liner, for example, a flexible plastic film can be cited. As the plastic film, for example, a polyethylene terephthalate film, a polyethylene film, a polypropylene film, and a polyester film can be cited. The thickness of the release liner is, for example, 3 μm or more, and for example, 200 μm or less. The surface of the release liner is coated with a release agent. Specific examples of the release agent include silicone-based release agents, fluorine-based release agents, and long-chain alkyl acrylate-based release agents.

[0125] F. Image display device

[0126] The polarizer with a phase difference layer can be applied to an image display device. Therefore, the image display device according to an embodiment of the present invention is equipped with the polarizer with a phase difference layer. As a representative example of the image display device, a liquid crystal display device and an electroluminescent (EL) display device (for example, an organic EL display device, an inorganic EL display device) can be cited.

[0127] Example

[0128] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that various measuring methods are as follows. In addition, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are based on weight.

[0129] (1) Thickness

[0130] The thickness of 1 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name “JSM-7100F”). The thickness exceeding 1 μm was measured using a digital micrometer (manufactured by Anritsu Ltd., product name “KC-351C”).

[0131] (2) In-plane phase difference Re(λ) and thickness direction phase difference Rth(λ)

[0132] The in-plane phase difference and the thickness direction phase difference at each wavelength at 23° C. were measured using a Mueller matrix polarimeter (manufactured by Axometrics, product name “Axoscan”).

[0133] (3) Refractive index

[0134] The average refractive index was measured using an Abbe refractometer manufactured by ATAGO Corporation, and the refractive indices nx, ny, and nz were calculated from the above-mentioned phase difference values.

[0135] (4) Durability

[0136] The polarizer with a phase difference layer obtained in the examples and comparative examples was cut into a size of 70 mm in length and 150 mm in width as a sample. In addition, it was cut in such a way that the slow axis direction of the second phase difference layer became the lateral direction of the sample. The second adhesive layer of the polarizer with a phase difference layer was bonded to a reflective plate (manufactured by Toray Film Processing Co., Ltd., trade name "Cerapeel DMS-X42", total light reflectance: 86%) and subjected to a durability test at 80°C for 500 hours. For the samples after the durability test, the hue a value and hue b value were measured using a spectrophotometer / colorimeter "CM-26d" manufactured by Konica Minolta, and the center (a * A , b * A ) and the end of the polarizing plate with a phase difference layer (a * B , b * B ) is set to Δa * b * In addition, the intersection of the diagonal lines of the polarizing plate with a phase difference layer is set as the center of the polarizing plate with a phase difference layer, and the end of the center line extending along the longitudinal direction (lateral direction) is set as the end of the polarizing plate with a phase difference layer.

[0137] Δa * b * =√(a * A -a* B ) 2 +(b * A -b * B ) 2

[0138] (5) Storage modulus G'

[0139] The measurement was performed at 25°C using a dynamic viscoelasticity device (viscoelasticity spectrometer, manufactured by Rheometric Scientific, Inc., “ARES device”).

[0140] [Manufacturing Example 1: Preparation of Polarizing Plate A]

[0141] (Production of Polarizer)

[0142] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.

[0143] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization: 4200, degree of saponification: 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, trade name "Gosenex Z410") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating solution).

[0144] The PVA aqueous solution was applied onto the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.

[0145] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).

[0146] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0147] Next, it was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 in 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained would reach a desired value (dyeing treatment).

[0148] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid into 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0149] Then, the laminate is immersed in an aqueous boric acid solution (boric acid concentration is 4 wt %, potassium iodide concentration is 5 wt %) at a liquid temperature of 70°C, and simultaneously uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio reaches 5.5 times.

[0150] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0151] Then, the film was brought into contact with a SUS heating roll whose surface temperature was maintained at about 75° C. while being dried in an oven maintained at about 90° C. (drying shrinkage treatment).

[0152] In this manner, a polarizer having a thickness of 5 μm was formed on the resin substrate.

[0153] (Production of Polarizing Plate A)

[0154] On the surface of the obtained polarizer (the surface on the opposite side to the resin substrate), an HC-TAC film is bonded as a protective layer using an ultraviolet curing adhesive. Specifically, the ultraviolet curing adhesive is applied in a manner to a thickness of 1.0 μm, and is bonded using a roller press. Then, UV light is irradiated from the protective layer side to cure the adhesive. It should be noted that the HC-TAC film is a film in which a hard coating (HC) layer (7 μm thick) is formed on a triacetylcellulose (TAC) film (25 μm thick), and the TAC film is bonded in a manner that is on the polarizer side. Next, the resin substrate is peeled off and removed to obtain a polarizer A having a structure of [polarizer / TAC protective layer with HC]. The single body transmittance of polarizer A is 43%, and the polarization degree is 99.9%.

[0155] [Manufacturing Example 2: Preparation of Positive C Plate]

[0156] In an autoclave equipped with a stirrer, a condenser, a nitrogen inlet tube and a thermometer, 48 parts by weight of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical, trade name: METOLOSE 60SH-50), 15601 parts by weight of distilled water, 8161 parts by weight of diisopropyl fumarate, 240 parts by weight of 3-ethyl-3-oxetanyl methyl acrylate and 45 parts by weight of tert-butyl peroxypivalate as a polymerization initiator were added, and nitrogen bubbling was performed for 1 hour, and then the mixture was kept at 49° C. for 24 hours while stirring to perform free radical suspension polymerization. Then, the mixture was cooled to room temperature, and the suspension containing the generated polymer particles was centrifuged. The obtained polymer was washed twice with distilled water and twice with methanol, and then dried under reduced pressure. The obtained fumarate resin was dissolved in a toluene / methyl ethyl ketone mixed solution (toluene / methyl ethyl ketone, 50% by weight / 50% by weight) to prepare a 20% solution. In addition, 5 parts by weight of tributyl trimellitate was added as a plasticizer to 100 parts by weight of a fumarate resin to prepare a dope. As a support film, a biaxially stretched film (thickness 75 μm) of polyester (polyethylene terephthalate / polyethylene isophthalate copolymer) was used. The prepared dope was applied to the support film in such a way that the film thickness after drying reached 28 μm, and dried at 140°C. Thus, a resin film (positive C plate A) showing a refractive index characteristic of nz>nx=ny was obtained. The thickness of the positive C plate A was 28 μm, the in-plane phase difference Re(550)≈0 nm, and the thickness direction phase difference Rth(550) was -135 nm.

[0157] [Manufacturing Example 3: Preparation of Negative B Plate]

[0158] In a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C., 29.60 parts by weight (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spiroglycol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC), and 1.19×10 mol of calcium acetate monohydrate as a catalyst were charged. -2 Weight parts (6.78×10 -5mol). After the reactor is replaced with nitrogen under reduced pressure, it is heated in a heat medium and stirring is started when the internal temperature reaches 100°C. After 40 minutes from the start of heating, the internal temperature reaches 220°C, and the pressure is reduced while being controlled to maintain the temperature. After reaching 220°C, it takes 90 minutes to reach 13.3kPa. The phenol vapor generated as a by-product along with the polymerization reaction is introduced into a reflux condenser at 100°C, and a certain amount of monomer components contained in the phenol vapor is returned to the reactor, and the uncondensed phenol vapor is introduced into a condenser at 45°C for recovery. After nitrogen is introduced into the first reactor and the pressure is temporarily restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor is transferred to the second reactor. Next, the heating and pressure reduction in the second reactor are started, and the internal temperature reaches 240°C and the pressure reaches 0.2kPa in 50 minutes. Then, the polymerization is carried out until the specified stirring power is reached. When a predetermined power was reached, nitrogen was introduced into the reactor to restore the pressure, and 0.7 parts by weight of PMMA was melt-kneaded with 100 parts by weight of the produced polyester carbonate resin, and then extruded into water, and the strands were cut to obtain pellets.

[0159] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a film-making device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., barrel setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a cooling roller (setting temperature: 120-130°C) and a winder was used to prepare a long strip of resin film with a thickness of 135 μm. The obtained long strip of resin film was stretched by about 2.8 times in the width direction at 133°C while adjusting the obtained long strip of resin film in a manner to obtain a predetermined phase difference, thereby obtaining a stretched film (negative B plate A) with a thickness of 48 μm showing a refractive index characteristic of nx>ny>nz. The Re(550) of the negative B plate A is 143 nm, the Nz coefficient is 1.1, and the Re(450) / Re(550) is 0.86.

[0160] [Production Example 4: Preparation of Adhesive A]

[0161] 1. Preparation of base polymer

[0162] A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate relative to 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while slowly stirring to replace the nitrogen. The liquid temperature in the flask was maintained at around 55°C and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to prepare a solution of a (meth)acrylic acid polymer with a weight average molecular weight of 2 million and a solid content concentration adjusted to 30%.

[0163] 2. Preparation of acrylic adhesive

[0164] Acrylic adhesive A was prepared by adding 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / toluene diisocyanate adduct, manufactured by Tosoh Corporation, trade name "Coronate L") and 0.1 parts by weight of a silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) to 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.

[0165] [Manufacturing Example 5: Preparation of Adhesive B]

[0166] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 74.9 parts by weight of butyl acrylate (BA), 20 parts by weight of benzyl acrylate (BzA), 5 parts by weight of acrylic acid (AA), 1 part by weight of 4-hydroxybutyl acrylate (HBA), 0.1 part of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 100 parts of ethyl acetate were added, and nitrogen gas was introduced while slowly stirring to replace the nitrogen. Then, the liquid temperature in the flask was maintained at around 55° C. and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight of 2.3 million. Acrylic adhesive B was prepared by adding 3 parts by weight of trimethylolpropane / toluene diisocyanate adduct (manufactured by Tosoh Corporation, trade name "Coronate L"), 0.2 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM403"), and 1 part by weight of a polyether compound having a reactive silyl group (manufactured by Kaneka Corporation, trade name "SILYLSAT10") to 100 parts by weight of the solid content of the obtained acrylic polymer solution.

[0167] [Manufacturing Example 6: Preparation of Adhesive C]

[0168] 1. Preparation of (meth)acrylic acid polymers

[0169] A monomer mixture containing 99 parts by weight of butyl acrylate (BA) and 1 part by weight of 4-hydroxybutyl acrylate (HBA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2′-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate relative to 100 parts by weight of the above monomer mixture (solid content), and nitrogen gas was introduced while slowly stirring to replace the nitrogen, and then the liquid temperature in the flask was maintained at around 55°C to perform a polymerization reaction for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to prepare a solution of a (meth)acrylic acid polymer with a weight average molecular weight of 1.6 million and a solid content concentration adjusted to 30%.

[0170] 2. Preparation of Acrylic Adhesive C

[0171] Acrylic adhesive C was prepared by adding 0.1 part by weight of an isocyanate crosslinking agent (trade name: Takenate D110N, trimethylolpropane benzyl diisocyanate, manufactured by Mitsui Chemicals, Inc.), 0.3 part by weight of a peroxide crosslinking agent (trade name: NyperBMT, manufactured by NOF Corporation), and 0.1 part by weight of a silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.), relative to 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.

[0172] [Manufacturing Example 7: Preparation of UV Curable Adhesive A]

[0173] An ultraviolet curing adhesive A was prepared by mixing 50 parts of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel Corporation, product name "PLACCELFA-1DDM"), 10 parts of polyethylene glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light acrylate 9EG-A"), 20 parts of acryloylmorpholine, 15 parts of an acrylic polymer (manufactured by Toagosei Co., Ltd., product name "ARUFON UP-1190"), 3 parts of a photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad 907"), and 2 parts of a photopolymerization initiator (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE-DETX-S") .

[0174] [Example 1]

[0175] On the polarizer of polarizer A, UV curing adhesive A was applied in a manner to a thickness of 1.0 μm, and the above-mentioned positive C plate was bonded. Next, adhesive A was applied on the positive C plate to form a first adhesive layer with a thickness of 15 μm, and the above-mentioned negative B plate was bonded. At this time, bonding was performed in a manner so that the slow axis direction of the negative B plate was at an angle of 45° clockwise relative to the absorption axis direction of the polarizer. Next, adhesive B was applied on the negative C plate to form a second adhesive layer with a thickness of 15 μm, and a polarizer with a phase difference layer having a structure of polarizer (HC-TAC / polarizer) / adhesive layer / positive C plate / first adhesive layer (adhesive A) / negative B plate / second adhesive layer (adhesive B) was obtained. During the evaluation period, a release liner was bonded on the second adhesive layer. The results are shown in Table 1.

[0176] [Example 2]

[0177] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that the first adhesive layer (thickness: 15 μm) was formed using the adhesive C. The results are shown in Table 1.

[0178] (Comparative Example 1)

[0179] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that the second adhesive layer (thickness: 15 μm) was formed using the adhesive A. The results are shown in Table 1.

[0180] (Comparative Example 2)

[0181] A polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 1 except that the first adhesive layer (thickness: 15 μm) was formed using the adhesive B. The results are shown in Table 1.

[0182] (Comparative Example 3)

[0183] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that the first adhesive layer (thickness: 15 μm) was formed using the adhesive B. The results are shown in Table 1.

[0184] Table 1

[0185]

[0186] As shown in Table 1, the polarizing plate with a retardation layer according to the embodiment of the present invention suppresses the deviation of the hue and is excellent in durability.

[0187] Industrial Applicability

[0188] The polarizing plate with a retardation layer according to the embodiment of the present invention can be used, for example, in an image display device. Representative examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device.

Claims

1. A polarizing plate with a phase difference layer, which comprises, in order: a polarizing plate including a polarizer; a first phase difference layer; a first adhesive layer; a second phase difference layer; and a second adhesive layer, The refractive index characteristics of the first retardation layer show the relationship of nz>nx=ny. The refractive index characteristics of the second retardation layer show the relationship of nx>ny≥nz. The first phase difference layer and the second phase difference layer are resin films. The storage modulus G' of the second adhesive layer AD2 More than 0.15MPa. 2 . The polarizing plate with a retardation layer according to claim 1 , wherein the polarizer and the first retardation layer are laminated via an adhesive layer.

3. The polarizing plate with a phase difference layer according to claim 1, wherein: The Re(550) of the second phase difference layer is 120nm to 170nm, The angle formed by the slow axis of the second phase difference layer and the absorption axis of the polarizer is 40° to 50° or 130° to 140°.

4. The polarizing plate with a phase difference layer according to claim 1, wherein: The second phase difference layer is a resin film containing a polycarbonate-based resin.

5. The polarizing plate with a phase difference layer according to claim 1, wherein: The storage modulus G' of the second adhesive layer AD2 The storage modulus G' of the first adhesive layer AD1 Meet G' AD2 >G' AD1 relationship. The polarizing plate with a phase difference layer according to claim 1 , which is used in an organic electroluminescent display device. 7 . An image display device comprising the polarizing plate with a retardation layer according to claim 1 . The image display device according to claim 7 , which is an organic electroluminescent display device.

Citation Information

Patent Citations

  • JP1974059014A

  • Optically active liquid crystal compound having cyano group

    JP1989070455A

  • Pressure-sensitive adhesive for optical film, pressure-sensitive adhesive layer for optical film, its manufacturing method, pressure-sensitive adhesive optical film and image display device

    JP2006183022A

  • multilayer optical compensator

    JP2008544304A

  • Multilayer compensation film using material with specific glass transition temperature

    JP2008544317A